2021
DOI: 10.3389/fcell.2020.611938
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Mitophagy: Friend or Foe?

Abstract: Maintenance of neuronal homeostasis is a challenging task, due to unique cellular organization and bioenergetic demands of post-mitotic neurons. It is increasingly appreciated that impairment of mitochondrial homeostasis represents an early sign of neuronal dysfunction that is common in both age-related neurodegenerative as well as in neurodevelopmental disorders. Mitochondrial selective autophagy, known as mitophagy, regulates mitochondrial number ensuring cellular adaptation in response to several intracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 118 publications
0
29
0
Order By: Relevance
“…Parkin overexpression affects mitophagy via two different mechanisms in early and later stages of IOP perturbations, suggesting that manipulating mitophagy might be harmful to some patients. Mitophagic hyperactivity can result in an inadequate ATP supply and eventually trigger neuronal cell death, which has attracted increasing attention ( Doxaki and Palikaras, 2020 ).…”
Section: Mitochondria Of Rgcs: Critical Target Of Metal Ionsmentioning
confidence: 99%
“…Parkin overexpression affects mitophagy via two different mechanisms in early and later stages of IOP perturbations, suggesting that manipulating mitophagy might be harmful to some patients. Mitophagic hyperactivity can result in an inadequate ATP supply and eventually trigger neuronal cell death, which has attracted increasing attention ( Doxaki and Palikaras, 2020 ).…”
Section: Mitochondria Of Rgcs: Critical Target Of Metal Ionsmentioning
confidence: 99%
“…Mitophagy is a form of autophagy that mediates the removal of defective or redundant mitochondria ( Doxaki and Palikaras 2020 ; Wang et al, 2021 ). And it is the only known way to selectively remove entire mitochondria ( D'Acunzo et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Stimulation of mitophagy has proven to be a promising therapeutic target for neurodegenerative diseases 69 and may be beneficial for healthy aging. Using a high-throughput, high-content phenotypic screen, we obtained and characterized eight compounds that lead to increased accumulation of PINK-1/PINK1.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of mitochondrial damage, and concomitant degradation of function, is associated with both aging and neurodegenerative disease. Mitophagy also appears to be inherently limited in mature neurons (reviewed in 69 ), which may explain why this tissue is more sensitive to mitochondrial damage in the first place. Increasingly, it has been hypothesized and demonstrated that increasing mitophagy in these cells may promote better cellular health and aging (reviewed in 69 ).…”
Section: Discussionmentioning
confidence: 99%